The geopolitics of climate change and violent conflicts in Africa: the Nigerian and Kenyan perspectives - Emupenne, Olanrewaju Ojo (University of the Witwatersrand, Johannesburg, 2024)
This study empirically examined the correlation between climate change (independent variable) and violent conflict (dependent variable), focusing on East Africa and West Africa. Climate change poses a serious threat to humanity and the ecosystem, particularly in Africa. Also, despite other serious challenges the continent faces, violent conflict remains among the most devastating. Various reasons, including poor leadership, social exclusion, and conflicting goals, are cited as causes of violent conflict in Africa. Recently, a new narrative has emerged suggesting climate change is a potential driver of violent conflicts. This study examines the correlation. So, to investigate this relationship, a survey research design was employed. The study adopted a descriptive research design, and four main research methods were used in the study namely, mixed methods research, comparative case study research, triangulation approach to social research, and convergent synthesis design. Also, the research utilized questionnaires that were directly formulated from the study’s hypotheses and were tested using a parametric regression model. Furthermore, the research employed Key Informant Interviews (KII), and the data gathered were processed using Atlas.ti, a Computer Assisted Qualitative Data Software (CAQDAS). Sampling techniques included purposive, stratified, and random sampling. The study population comprised government officials, environmentalists, academia, farmers, herders, youth leaders, and community leaders. 17 government officials, 7 academia, 6 environmentalists, 15 farmers, and 13 herders randomly selected in Nigeria, and 22 government officials, academia, and environmentalists, 15 farmers and members of farmers cooperatives, and 12 herders and members of livestock associations randomly selected in Kenya participated in the Key Informant Interviews (KIIs) to make a sample size of 110. In addition, 174 government officials, environmentalists, and academics completed the Set A questionnaire in Nigeria, 116 government officials, environmentalists, and academics completed the Set A questionnaire in Kenya, and 423 farmers, herders, youths, and community leaders completed the Set B questionnaire in Nigeria, and 205 respondents do the same in Kenya to make a sample of 918 respondents. In all, a total of 1,028 respondents participated in the study. The study was systematically guided by four research questions and two hypotheses. These research questions are as follows: (1) To what extent does climate change effect features in the geopolitics of peace and security in West Africa and East Africa? (2) Specifically, what is the correlation between climate change and farmer-herder conflicts in the Middle Belt region of Nigeria and farmer-herder conflicts in the Tana River County in Kenya? (3) What is the level of awareness about the effects of climate change among crop farmers, herders, and policymakers in the Northern region of Nigeria and Tana River County of Kenya, and how does the knowledge about the effects of climate change play a role in the different stakeholders’ approach to conflict? (4) What are the policy frameworks in Nigeria and Kenya that create awareness about climate change and mitigate the effects vi of climate change on violent conflict at both national and local levels? The quantitative data obtained were analyzed using SPSS Version 25 and R, while the qualitative data were analyzed using Atlas.ti. Results revealed a positive correlation between climate change and geopolitical dynamics of peace and security in West Africa and East Africa but did not establish causation. While climate change intensified, it contributed to shifts in geopolitical dynamics impacting peace and security. However, establishing causation requires more than observing correlation; it demands demonstrating that changes in the independent variable cause changes in the dependent variable. The findings of the study also revealed varying levels of knowledge and awareness regarding climate change among farmers, herders, and policymakers in Northern Nigeria and Tana River County of Kenya; divergent opinions about available policy frameworks for creating awareness about climate change and mitigating the effects of climate change on violent conflict. Some of the respondents agreed that policies were available, some were of the view that policies were available but not implemented while some expressed the fact that policies were not available. Considering these findings, several policy recommendations were made which include the integration of climate adaptation strategies with conflict prevention efforts, decision- making and policy implementation, creating more awareness programmes, indigenous approach and inclusivity, curbing migration, farmer/herder dialogue, and the establishment of special judicial commission solely for farmers and herders. In a nutshell, the study emphasized the need for nuanced understanding and consideration of multiple factors influencing the geopolitical landscape of Africa
A research report Submitted in fulfillment of the requirements for a f Doctor of Philosophy in International Relations, In the Faculty of Humanities , School of Social Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Climate Change; Farmers; Herders; Geopolitics; Violent Conflict; SDG-13: Climate action